Gamification, Live Streaming, and Social Influence as Drivers of Purchase Intention: The Mediating Role of Flow Experience among Generation Z - Lucky Radi Rinandiyana; Dian Kurniawan; Alfin Nur Fahmi Mufreni; Tine Badriatin (Almana : Jurnal Manajemen dan Bisnis, 2026)
The rapid growth of e-commerce and digital marketing has transformed Generation Z’s online shopping behavior, highlighting the need to understand how digital marketing stimuli influence purchase intention. This study aims to analyze the influence of gamification, live streaming, and social influence on Generation Z’s purchase intention in Priangan Timur, with flow experience as a mediating variable. A quantitative survey involving 300 respondents was analyzed using Structural Equation Modeling (SEM). The results indicate that gamification, live streaming, and social influence significantly influence flow experience, which subsequently has a significant positive effect on purchase intention. Mediation analysis demonstrates that flow experience partially mediates the relationships between the three digital stimuli and purchase intention, with live streaming producing the strongest indirect effect. These findings confirm the central role of flow experience within the Stimulus–Organism–Response (SOR) framework and highlight its importance in developing experience-based digital marketing strategies. The study’s novelty lies in integrating gamification, live streaming, and social influence into a unified SOR model while positioning flow experience as the key mediating mechanism. Future research should validate the model across different regions, generations, and digital platforms by incorporating trust, perceived enjoyment, and AI-powered personalization.